Performance of honeycomb sandwich slab panel with different depth and internal angle in terms of deflection and failure mode using ABAQUS - Tan, Yi Koon (2016)
Honeycomb sandwich slab panel (HSSP) is one of the type of composite slab which made up honeycomb structure core layer cover by concrete both top and bottom. Core layer made up of carbon fiber reinforced plastic. The main objectives of the study were to simulate the deflection and failure mode of HSSP due to different internal angle and depth of honeycomb structure core layer by using ABAQUS v6.14 Finite Element Analysis Software. Seven models designated as HSSP 1, HSSP 2, HSSP 3, HSSP 4, HSSP 5, HSSP 6 and HSSP 7. Where HSSP 1, HSSP 2, HSSP 3 and HSSP 4 with internal angle of 15 o, 30 o, 45 o and 60 o respectively. HSSP 5, HSSP 6 and HSP 7 are models different in depth of honeycomb sandwich core layer which is 120 mm, 130 mm and 140 mm respectively. The deflection of the HSSP 4 was 31.23 mm. The results showed inversely proportional relation between internal angle and deflection. While for depth of honeycomb sandwich core layer showed inversely proportional relation between depth of core layer and deflection. HSSP 7 deflected 26.74 mm according to simulation by ABAQUS.